Testing isotropy in the Two Micron All-Sky redshift survey with information entropy. Issue 2 (7th March 2017) - Pandey, Biswajit
Abstract: We use information entropy to test the isotropy in the nearby galaxy distribution mapped by the Two Micron All-Sky redshift survey (2MRS). We find that the galaxy distribution is highly anisotropic on small scales. The radial anisotropy gradually decreases with increasing length-scales and the observed anisotropy is consistent with that expected for an isotropic Poisson distribution beyond a length-scale of 90  h −1  Mpc. Using mock catalogues from N -body simulations, we find that the galaxy distribution in the 2MRS exhibits a degree of anisotropy compatible with that of the Λ cold dark matter (ΛCDM) model after accounting for the clustering bias of the 2MRS galaxies. We also quantify the polar and azimuthal anisotropies and identify two directions ( l, b ) = (150°, −15°), ( l, b ) = (310°, −15°) that are significantly anisotropic compared to the other directions in the sky. We suggest that their preferential orientations in the sky may indicate a possible alignment of the Local Group with two nearby large-scale structures. Despite the differences in the degree of anisotropy on small scales, we find that the galaxy distributions in both the 2MRS and the ΛCDM model are isotropic on a scale of 90  h −1  Mpc.